2009
DOI: 10.1002/ange.200806334
|View full text |Cite
|
Sign up to set email alerts
|

High Catalytic Activity of Palladium(II)‐Exchanged Mesoporous Sodalite and NaA Zeolite for Bulky Aryl Coupling Reactions: Reusability under Aerobic Conditions

Abstract: Wechsel zum Besseren: Mesoporöse Sodalit‐ und NaA‐Zeolithe, die durch Ionenaustausch mit Pd2+ beladen wurden, zeigen bemerkenswerte Aktivitäten in C‐C‐Kupplungen unter aeroben Bedingungen und können mehrfach verwendet werden. Die Katalyseschritte werden vermutlich durch in situ gebildete Pd0‐Spezies vermittelt (siehe Bild), die durch O2 zu Pd2+ rückoxidiert werden, was die Bildung katalytisch inaktiver Pd0‐Agglomerate verhindert.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…[18][19][20] Different supports have been reported for immobilization of palladium catalysts recently, including sepiolites, 21,22 hydrotalcite, 23 silica, 24 fluorous silica gel, 25,26 zeolite, [27][28][29] carbon, 30 and so on. 31 A few palladium complexes supported on functionalized polymer have been reported in some reactions successfully.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Different supports have been reported for immobilization of palladium catalysts recently, including sepiolites, 21,22 hydrotalcite, 23 silica, 24 fluorous silica gel, 25,26 zeolite, [27][28][29] carbon, 30 and so on. 31 A few palladium complexes supported on functionalized polymer have been reported in some reactions successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Successful reports include the synthesis of mesoporous LTA [ 119 , 124 ], SOD [ 126 ], and BEA [ 127 ] zeolite architectures and the synthesis of mesoporous aluminophosphates constructed with crystalline microporous AFI and AEL topologies [ 128 ]. Recent reports claimed the synthesis of X zeolite (FAU topology) with high Al content (Si/Al < 1.5), exhibiting a pore system in a micro-meso-macro hierarchical interconnection [ 129 ].…”
Section: Use Of Organosilane Molecules As Mesopore-generating Agentsmentioning
confidence: 98%
“…To solve such problem, a novel ligand‐protected exchange method was developed. With the protection of ammonia, cationic complexes Pt(NH 3 ) 4 2+ , Pd(NH 3 ) 4 2+ , and Ir[(NH 3 ) 5 Cl] 2+ were stabilized in solutions, ensuring that these metal species could encapsulated into zeolites during the ion‐exchange process . This approach led to several ultrasmall Pt clusters being successfully encaged within zeolites, including MFI , LTL , BEA and FAU .…”
Section: Metal Clusters Confined In Zeolitesmentioning
confidence: 99%
“…This approach led to several ultrasmall Pt clusters being successfully encaged within zeolites, including MFI , LTL , BEA and FAU . [20e,21] Notably, when [Pt(NH 3 ) 4 ](NO 3 ) 2 solution was used as the exchange precursor, atomically dispersed Pt was also successfully embedded in KLTL zeolite. [21a] Utilizing high‐resolution scanning transmission electron microscopy (STEM), the authors confirmed that most of the isolated Pt(NH 3 ) 4 2+ cations were located at the edge of the 12 rings in zeolites and that only a few Pt(NH 3 ) 4 2+ cations were situated at the small rings between the 12 rings ( Figure A–D).…”
Section: Metal Clusters Confined In Zeolitesmentioning
confidence: 99%